How to Cultivate Students’ Interests in Physics: A Challenge for Senior High School Teachers - Tomo Djudin (Jurnal Pendidikan Sains, 2018)
Abstract: Interest may be seen as the medium and the goal of educational processes. Students will learn physics better, and moreover, choose physics course intentionally if they are interested in it. Unfortunately, over the last two decades a persistent decline of students’ interest in physics has found in many countries. This literature review mainly focused on student’s interest in physics. It is concluded that the influential factors which cause students to disinterested in physics are: (1) they were lack of familiarity with physics; (2) they regarded physics as the most difficult science; (3) most school science courses rely on a large amount of memorization or rote learning; and (4) they are admittedly worried about failing the class. In addition, lack of student interest can be quite a challenge for teachers to combat such as by applying teaching-based technology, using project-based learning, increasing human being context or making cross-curricular connections, and showing the use of physics concept in the future. Teachers can cultivate students’ situational interest to personal interest by revitalizing contents (topics), context, and learning activity in conjunction with the content and context.Key Words: students’ interests, factors affecting interest, challenges for physics teachersAbstrak: Minat dapat dilihat sebagai media dan tujuan dari proses pendidikan. Siswa akan belajar fisika lebih baik, dan terlebih lagi, memilih mata pelajaran fisika dengan sengaja jika mereka tertarik. Sayangnya, selama dua dekade terakhir, penurunan minat siswa yang terus-menerus terhadap fisika telah ditemukan di banyak negara. Kajian literatur terutamanya berfokus pada minat siswa dalam fisika. Dapat disimpulkan bahwa faktor-faktor berpengaruh yang menyebabkan siswa tidak tertarik pada fisika adalah: (1) mereka kurang mengenal fisika; (2) mereka menganggap fisika sebagai ilmu yang paling sulit; (3) sebagian besar program sekolah bergantung pada sejumlah besar penghafalan atau pembelajaran hafalan; dan (4) mereka khawatir akan kegagalan dalam kelas. Selain itu, kurangnya minat siswa dapat menjadi tantangan bagi guru untuk mengatasi permasalahan tersebut dengan menerapkan teknologi berbasis pengajaran, menggunakan pembelajaran berbasis proyek, meningkatkan konteks manusia atau membuat koneksi lintas-kurikuler, dan menunjukkan penggunaan konsep fisika di masa depan. Guru dapat menum-buhkan minat situasional siswa untuk minat pribadi dengan menghidupkan konten (topik), konteks, dan aktivitas pembelajaran bersama dengan konten dan konteksnya.Kata kunci: minat siswa, faktor-faktor yang mempengaruhi minat, tantangan guru fisika